Legal Impact of Female Genital Mutilation: Special Reference to Penal Laws and Human Rights Perspective in the Criminal Justice System of Sri Lanka. Issue 2 (December 2019) - Wijayath, Aruni
Female genital mutilation (FGM) is a ritual and religious and cultural practice among the Moor, Malay and Dawoodi Bohra ethnic communities in Sri Lanka. The process of FGM is ensconced from the general public in Sri Lanka; therefore, few pieces of research pertaining to the practice of FGM are available. A considerable number of international organizations profess that the percentage of FGM/cutting is zero in Sri Lanka through their reports, although newspaper articles and country reports disclose that FGM actually exists among the Muslim community in Sri Lanka. The knowledge regarding the process of FGM is in the backwater in Sri Lanka, even though a considerable number of feminism activists have created a platform to discuss the bad consequences emerging from this harmful practice. According to the World Health Organization (WHO), 30 countries of African Region, selected countries in the Middle East, and countries of Asian Region practice this custom among the female community in some ethnic and religious groups. Through this practice, the female community has not gained any advantage or benefit. The purpose of this research is to explore the municipal laws and human rights regarding FGM in the Sri Lankan context. Furthermore, international conventions which are ratified by Sri Lanka will be analysed in this manner. This research is mainly based on the normative method and retrieved Internet documentary analysis in a qualitative manner.